2019
DOI: 10.1021/acs.orglett.9b01297
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)-Catalyzed Oxidation of Acyl Acetylenes to Vicinal Tricarbonyls

Abstract: Efficient gold(I)-catalyzed oxidation of COR 2 -functionalized internal alkynes to vicinal tricarbonyl compounds by 2,6-dichloropyridine N-oxide proceeds under mild conditions (DCM, rt). This catalytic reaction provides a good to excellent yielding route to diverse tricarbonyls such as α,β-diketoesters, 1,2,3-triketones, and α,β-diketoamides. The utility of these compounds was also demonstrated by facile one-pot synthesis of important azaheterocyclic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…They can be converted into several types of heterocycles using one-pot transformations (Scheme B) . 1,2,3-Tricarbonyl compounds can also be obtained using the same strategy . K. Severin reported that the C–C triple bond of alkynyl triazenes can be similarly double-oxidized under gold catalysis as long as the carbene 1,2-C–H insertion pathway is not available …”
Section: Reactions Without Metal Oxidation State Changementioning
confidence: 99%
See 1 more Smart Citation
“…They can be converted into several types of heterocycles using one-pot transformations (Scheme B) . 1,2,3-Tricarbonyl compounds can also be obtained using the same strategy . K. Severin reported that the C–C triple bond of alkynyl triazenes can be similarly double-oxidized under gold catalysis as long as the carbene 1,2-C–H insertion pathway is not available …”
Section: Reactions Without Metal Oxidation State Changementioning
confidence: 99%
“…54 1,2,3-Tricarbonyl compounds can also be obtained using the same strategy. 56 K. Severin reported that the C−C triple bond of alkynyl triazenes can be similarly double-oxidized under gold catalysis as long as the carbene 1,2-C−H insertion pathway is not available. 57 In 2011, L. Zhang extended this type of oxidative gold catalysis to terminal allene substrates.…”
Section: Reactions Without Metal Oxidation State Change 21 Activated ...mentioning
confidence: 99%
“…Moreover, alkynyl esters, amides and ketones are efficiently converted into their corresponding vicinal tricarbonyls under mild conditions without any acid additives (Scheme 7). [29] In some cases, the isolated products were mixture of keto and their hydrated form. When NÀ O oxidant is employed, the reduced oxidant can subsequently act as N-nucleophile resulting in oxoamination of alkyne.…”
Section: Oxidative 12-difunctionalizations Of Alkynesmentioning
confidence: 99%
“…While the cyclopropanation of related α-oxo carbenes is known, NT reactions utilizing α-imino carbenes are quite poorly explored: Hashmi and co-workers reported the only gold-catalyzed cyclopropanation of α-imino carbenes generated from anthranils and sulfilimines functioning as NTRs. Inspired by these works and on the basis of our previous experience in gold catalysis, we hypothesized that benzofuroxans could also serve as a source of gold α-imino carbenes for intramolecular cyclopropanation (Scheme C). We also addressed N -allylynamides, as the reaction partners, in view of their high reactivity in the catalytic annulations and facile customization of their substitution pattern. …”
Section: Introductionmentioning
confidence: 99%